A Low Crizotinib Concentration in the Cerebrospinal Fluid Causes Ineffective Treatment of Anaplastic Lymphoma Kinase-positive Non-small Cell Lung Cancer with Carcinomatous Meningitis - Okimoto, Tamio (Intern Med, 2018)
The central nervous system is a common site of relapse in patients receiving crizotinib, which is presumed to be associated with the low concentration of crizotinib in the cerebrospinal fluid (CSF). Our patient received surgical treatment for anaplastic lymphoma kinase-positive stage IIA lung adenocarcinoma. His cancer recurred with brain metastases and carcinomatous meningitis. We started whole-brain radiation therapy (WBRT) and subsequently administered crizotinib. The concentration of crizotinib on day 15 in the plasma was 158 ng/mL, and that in the spinal fluid was 4.32 ng/mL. WBRT may elevate the CSF/plasma crizotinib concentration ratio; clinicians may therefore consider performing WBRT prior to crizotinib initiation.